2015
DOI: 10.1002/2015jb011934
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution in bitaxial crack‐seal veins: A phase‐field study

Abstract: Bitaxial crack sealing by epitaxial crystal growth is the most common vein‐forming process in Earth's crust, but the details of the microstructural processes in these are not well understood. Here we model the evolution of bitaxial crack‐seal quartz veins in two and three dimensions, using the phase‐field method. Our numerical simulations show the influence of different parameters, such as the obliquity of crack opening and crack location, grain size, and orientations on the evolving vein microstructure. We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…Such models are enticing because they have the potential to predict textures and morphologies that may be compared directly with data from natural samples and laboratory experiments and because they serve as a more rigorous basis for predicting a wide range of rock properties compared with the model types discussed above. To date, most grain/pore scale simulation studies either have involved imposing a predefined diagenetic state as a means to rigorously simulate the impact of diagenetic alteration on bulk rock properties (Bakke & Øren 1997;Øren & Bakke 2002Øren & Bakke , 2003Øren et al 2007;Jin et al 2012;Mousavi & Bryant 2013;Prodanovic et al 2013;van der Land et al 2013;Hosa & Wood 2017) or consider a subset of the diagenetic processes that affect reservoir quality (Abe & Mair 2005;Lander et al 2008a;Marketos & Bolton 2009;Gale et al 2010;Cheung et al 2013;Ankit et al 2015;Lander & Laubach 2015;Wendler et al 2016). Although the promise of models of this class is enormous, considerable work is needed to develop comprehensive modelling approaches that are capable of making accurate pre-drill predictions.…”
Section: Experimental Simulation Of Diagenesismentioning
confidence: 99%
“…Such models are enticing because they have the potential to predict textures and morphologies that may be compared directly with data from natural samples and laboratory experiments and because they serve as a more rigorous basis for predicting a wide range of rock properties compared with the model types discussed above. To date, most grain/pore scale simulation studies either have involved imposing a predefined diagenetic state as a means to rigorously simulate the impact of diagenetic alteration on bulk rock properties (Bakke & Øren 1997;Øren & Bakke 2002Øren & Bakke , 2003Øren et al 2007;Jin et al 2012;Mousavi & Bryant 2013;Prodanovic et al 2013;van der Land et al 2013;Hosa & Wood 2017) or consider a subset of the diagenetic processes that affect reservoir quality (Abe & Mair 2005;Lander et al 2008a;Marketos & Bolton 2009;Gale et al 2010;Cheung et al 2013;Ankit et al 2015;Lander & Laubach 2015;Wendler et al 2016). Although the promise of models of this class is enormous, considerable work is needed to develop comprehensive modelling approaches that are capable of making accurate pre-drill predictions.…”
Section: Experimental Simulation Of Diagenesismentioning
confidence: 99%
“…Such an optimization results in highly efficient computation which is independent of N, facilitating 3D large-scale numerical studies. The multiphase-field model presented here has previously been employed by Ankit et al (2015) for studying microstructural evolution in bitaxial crack seal veins and Wendler et al (2015) for modeling of epitaxial growth of polycrystalline quartz veins.…”
Section: Model Formulation: Multiphase-field Modelmentioning
confidence: 99%
“…Ankit et al (2015) emphasized the role of curvature of grains in the formation of grain boundary patterns in rocks. These curvatures are different in 3D as compared to 2D which might result in erroneous interpretations.…”
mentioning
confidence: 99%
“…Because,i nm ost cases,f racture surfaces are mismatched to each other, the resultingm echanical and hydraulic apertures facilitate fluid flow and also fluid-inducedr eactive transport processes,w hich can affect hydraulic and mechanicalf racture properties. [31] In particular,f racture sealingp lays an importantr ole when considering time-dependentr eservoir scaling and activation or utilization of (partly) sealed structures.T hermodynamically consistent PFMs provide au seful numerical tool that is able to reproduce polycrystalline sealing scenarios, such as tectonically unaffected crystal growth [32] or syntectonic crack-seal processes. [31,33,34] Wendler et al showed that PFMs were able to reproduceh ydrothermal quartz growth experiments ( Figure 6I).…”
Section: Multiscale Fluid Flow In Fracturesmentioning
confidence: 99%
“…[31] In particular,f racture sealingp lays an importantr ole when considering time-dependentr eservoir scaling and activation or utilization of (partly) sealed structures.T hermodynamically consistent PFMs provide au seful numerical tool that is able to reproduce polycrystalline sealing scenarios, such as tectonically unaffected crystal growth [32] or syntectonic crack-seal processes. [31,33,34] Wendler et al showed that PFMs were able to reproduceh ydrothermal quartz growth experiments ( Figure 6I). [20] Hence, such models provide new insights into various sealings tructures andc orresponding flow paths.T of ate,P FMs have only been used to simulate pure sealing processes on micro-to millimeter scales.H owever, under reservoir conditions,t here should be an interaction of precipitation and dissolution processes, as shown in core-scale reactive percolation experiments under high pressure-temperature conditions with CO 2 -rich brines.…”
Section: Multiscale Fluid Flow In Fracturesmentioning
confidence: 99%